Discussion of the relationship between the longitudinal changes in lean body mass and the performance of young elite female soccer players - Matsuda, T.; Kiyonaga, K.; Mamizuka, N.; Hiyama, S.; Goto, M.; Tateishi, T.; Kato, H.; Dohi, M. (Journal of High Performance Sport, 2019)
Purpose: A decrease in the performance of female soccer players is observed from junior high school to senior high school, and anemia is often noted in tall, well-built players. In order to examine the involvement of low energy availability in that phenomenon, the current study examined changes in lean body mass with age in adolescent and post-adolescent female soccer players. Methods: We investigated changes associated with the development of lean body mass in correlation with skeletal muscle mass by monthly measuring body composition in elite female soccer players who were boarding students at a junior or senior high school, and analyzing longitudinal changes in lean body mass based on the measurement results. Results: Height and lean body mass were found to be correlated: a greater lean body mass was correlated with a taller height. The annual increase in lean body mass decreases as the growth in height slows, but temporarily increases from the age of 15 to 16 years. Increases in body weight during this period were approximately equal to increases in lean body mass. Conclusion: The temporary increase in lean body mass from age 15 to 16 was considered to be specific to female soccer players, and was thought to reflect an increase in skeletal muscle mass as a result of training. Because increases in lean body mass during this period is accompanied by an increase in basal metabolism, energy intake must be increased to avoid a low energy availability. This period of an increase in lean body mass coincides with a period of increases in testosterone levels and red blood cells, suggesting that these phenomena may affect one another. During this period, female soccer players should manage their body composition in terms of their lean body mass rather than in terms of their body weight or body mass index.